How bulimia nervosa relates to addictive behavior - Daniela Iorio; Michelle Sovinsky (University of Zurich, Department of Economics, 2012)
Using longitudinal data that tracks bulimic behavior among young girls (National Heart, Lung, and Blood Institute Growth and Health Study), we examine (1) whether bulimic behavior is onsistent with addiction criteria as stated in the Diagnostic and Statistical Manual of Mental Disorders DSM-IV (APA, 1994); and 2) whether the persistence in bulimia nervosa (BN) reflects tolerance formed from an addiction or if it can be attributed to slow learning about the deleterious health effects of BN. Making the case for treating BN as an addiction has important policy implications. First, it suggests that the timing of educational policy and treatment is crucial: preventive educational programs aimed at instructing girls about the deleterious health effects of BN, as well as treatment interventions, will be most effective if provided in the early stages. Second, it would put those exhibiting BN on more equal footing (from a treatment reimbursement perspective) with individuals with drug or alcohol addictions.
Keywords: I1; 330; Eating disorders; Bulimia Nervosa; Addiction; Ernährungsverhalten; Psychische Störung; Mädchen; USA